Baltų ir slavų kalbų vardažodžių daryba (senosios bendrybės ir skirtybės) - Ambrazas, Saulius (Baltistica, 1992)
WORD FORMATION OF NOUNS IN BALTIC AND SLAVIC (old common traits and differences) The article deals with the problem of relations of Baltic and Slavic languages on the base of word formation of nouns. Some archaic features of Slavic word formation in comparison with Baltic one are distinguished: 1) nomina agentis with old Indo-European suffix *-tel- were left whale in Slavic, but they were completly pushed out by the corresponding derivatives with new suffixes *-tāi̯o- (<*-tā- +* -i̯o-), *-ēi̯o- (<*ē + *-i̯o- ) in Baltic; 2) the adjectives with suffix *-(i)i̯o- kept their produktivity in Slavic, but they were replaced by the corresponding derivatives with suffixes *-ino-, *-ini̯o(<* -ino- +*-i̯o*) in Baltic; 3) the substantives with old Indo-European suffix *-mo- were also productive in Common Slavic, but they were changed by the derivatives with new suffixes *-i-mo-, *-u-mo- in Baltic. There are some mor old differences in Baltic and Slavic word formation. The suffix * -(i)i̯o- was often used on the formation of nomina collectiva in Slavic and in many other Indo-European languages (cf. Slav, sъnьje, Skt. svapn(i)yam, Lat. somnium, Gk. έν-υχνιον, Lith. sapnỹs “dream”), but this type of derivatives is almost unknow in Baltic. Nomina deminutiva with suffix *-iko- (<i + *-ko-) are very productive in Slavic, but they become extinct in Baltic (especialy in East Baltic). On the other hand the related suffix *-uko- (< u+*-ko-) is mor frequently used in this case in Baltic than in Slavic is. Some suffixes have a different form but a similar function in Baltic than in Slavic, cf. Balt. *-ībā- (<ī +*-bhā-) and Slav. *-iba (<i + -bhā-), Balt. *-ūno-(<ū + *-no-) and Slav. -uns (<u/ou + *-no-). Thees and other differences shows that the Proto-Slavic system of the word formation can be hardly derived direct from Proto-Baltic one. They could be better explained on the base of well known devergence theory, according to which the Baltic and the Slavic languages were descended from the different dialects of the north area of Indo-European parent language and only a bit later the period of close contacts of Proto-Baltic and Proto-Slavic came. There are some inovations in Baltic, Slavic and Germanic, which came of on the period, when thees three groups of languages were not separated from the north dialect area of Indo-European. One of thees inovations is sugested to be the suffix *- īti̯o - (<*-īto- + -i̯o-), the oldest function of which is the formation of nomina atributiva (cf. Lith. ausỹtė “wintry cap with ear-tabs"”, Latv. lēnītis “warm south or west wind”, South Slav. golit’ь “naked, poor man”). Through the process of the meaning specialization the derivatives with suffix *- īti̯o - got the meaning of nomina deminutiva in Baltic (cf. Lith. sūnỹtis, Latv. sūnītis “a little son”), the meaning of nomina patronimica and originis in Slavic (cf. Slav, bratit’ь “a brothes son”, slobodit’ь “countryman from a free land”) and the meaning of nomina collectiva in Germanic (cf. MHG. geveterīde “parents”). Later on the period of close contacts of Proto-Baltic and Proto-Slavic languages some derivatives with this suffix got also the meaning of nomina patroninica and nomina originis in Baltic dialects (especialy in West Baltic, cf. Lith. dial, vókytis, Latv. vācītis “German”) from Proto-Slavic and some of them got the meaning of nomina deminutiva in South Slavic languages (cf. vl̥’čit’ь „a little wolf-cub”) from Proto-Baltic. There are some old inovations which came of in Proto-Baltic and later feld under the Proto-Slavic language. In this way the development of nomina agentis with suffixes *- tāi̯o- (cf. Lith. artójas, OPruss. artoys E 236, Slav ratajь “ploughman, fanner”), *-ēi̯o- (cf. Lith. siuvė́jas, Latv. šuvējs, ORuss. šьvej “tailor”), *-iko- (cf. Lith. siuvìkas, OPruss schuwikis (Schuwert) E 496, Slav. šьvьcь “tailor”) which is very productive in Baltic and very rare in Slavic, could be explained. The process of a substitution of old suffixes with o stem for corresponding suffixes with (i)i̯o stem is sugested to come of in Baltic and to touch slightly Slavic languages too. The result of this process is the formation of Common Baltic and Slavic suffixes *-eli̯o- (from *- elo-), *-ēli̯o- (from *-ēlo-), *-ōli̯o- (from *-ōlo-), *-iki̯o- (from * -iko-).